Inside Out: Muslim women exploring identities and creative expressions 2004-2006 (Auburn Community Development Network Project, 2006)
Exhibition catalog. Exhibition May-Jun 2006 @Auburn Central, Sydney. The Inside Out exhibition is the culmination of an Auburn Community Development Network project, in partnership with community organisations and sponsors, artists and community participants. The project evolved over 3 years including research and development, cultural action, and exhibition production.
English
Keywords: Muslim diaspora; N4390-5098 Visual Arts. Exhibitions; Women Artists; Australia